Prognostic impact of total and tyrosine phosphorylated GIV/Girdin in breast cancers. Issue 11 (20th July 2016) - Dunkel, Ying; Diao, Kexin; Aznar, Nicolas; Swanson, Lee; Liu, Lawrence; Zhu, Wenhong; Mi, Xiao‐yi; Ghosh, Pradipta
ABSTRACT: Gα‐interacting vesicle‐associated protein (GIV, aka Girdin) is a guanine exchange factor (GEF) for the trimeric G protein Gαi and a bona fide metastasis‐related gene that serves as a platform for amplification of tyrosinebased signals via G‐protein intermediates. Here we present the first exploratory biomarker study conducted on a cohort of 187 patients with breast cancer to evaluate the prognostic role of total GIV (tGIV) and tyrosine phosphorylated GIV (pYGIV) across the various molecular subtypes. A Kaplan‐Meier analysis of recurrence‐free survival showed that the presence of tGIV, either cytoplasmic or nuclear, carried poor prognosis, but that nuclear tGIV had a greater prognostic impact ( P = 0.007 in early and P = 0.0048 in late clinical stages). Activated pYGIV in the cytoplasm hadthe greatest prognosticimpact inlate clinical stages ( P = 0.006). Furthermore, wefound that theprognostic impacts of cytoplasmic pYGIV and nuclear tGIV were additive (hazard ratio 19.0548; P = 0.0002). Surprisingly, this additive effect of nuclear tGIV/cytoplasmic pYGIV was observed in human epidermal growth factor receptor 2–positive tumors (hazard ratio 16.918; P = 0.0005)butnot in triple‐negative breast cancers. Intriple‐negative breast cancers, tGIV and cytoplasmic pYGIV had no prognostic impact; however, membrane‐association of pYGIV carried a poor prognosis ( P = 0.026). Both tGIV and pYGIV showed no correlationwith clinical stage, tumor size, pathologic type, lymph node involvement, and BRCA1/2 status. We conclude that immunocytochemical detection of pYGIV and tGIV can serve as an effective prognosticator. On the basis of the differential prognostic impact of tGIV/pYGIV within each molecular subtype, we propose a diagnostic algorithm. Further studies on larger cohorts are essential to rigorously assess the effectiveness and robustness of this algorithm in prognosticating outcome among patients with breast cancer.—Dunkel, Y., Diao, K., Aznar, N., Swanson, L., Liu, L., Zhu, W., Mi, X.‐Y., Ghosh, P. Prognostic impact of total and tyrosine phosphorylated GIV/Girdin in breast cancers. FASEB J. 30, 3702–3713 (2016) www.fasebj.org